Serum neuregulin 4 is negatively correlated with insulin sensitivity in humans and impairs mitochondrial respiration in HepG2 cells - Martínez, Cristina; Latorre, Jèssica; Ortega, Francisco; Arnoriaga-Rodríguez, María; Lluch, Aina; Oliveras-Cañellas, Núria; Díaz-Sáez, Francisco; Aragonés, Julian; Camps, Marta; Gumà, Anna; Ricart, Wifredo; Fernández-Real, José Manuel; et al. (Frontiers in Physiology, 2022)
Neuregulin 4 (NRG4) has been described to improve metabolic disturbances linked to obesity status in rodent models. The findings in humans are controversial. To investigate circulating NRG4 in association with insulin action in humans and the possible mechanisms involved. Insulin sensitivity (euglycemic hyperinsulinemic clamp) and serum NRG4 concentration (ELISA) were analysed in subjects with a wide range of adiposity (n=89). In vitro experiments with human HepG2 cell line were also performed. Serum NRG4 was negatively correlated with insulin sensitivity (r=-0.25, p=0.02) and positively with the inflammatory marker high-sensitivity C reative protein (hsCRP). In fact, multivariant linear regression analyses showed that insulin sensitivity contributed to BMI-, age-, sex- and hsCRP-adjusted 7.2% of the variance in serum NRG4 (p=0.01). No significant associations were found with adiposity measures (BMI, waist circumference or fat mass), plasma lipids (HDL-, LDL-cholesterol or fasting triglycerides) or markers of liver injury. Cultured hepatocyte HepG2 treated with human recombinant NRG4 had an impact on hepatocyte metabolism, leading to decreased gluconeogenic- and mitochondrial biogenesis-related gene expression, and reduced mitochondrial respiration, without effects on expression of lipid metabolism-related genes. Similar but more pronounced effects were found after neuregulin 1 administration. In conclusion, sustained higher serum levels of neuregulin-4, observed in insulin resistant patients may have deleterious effects on metabolic and mitochondrial function in hepatocytes. However, findings from in vitro experiments should be confirmed in human primary hepatocytes.